2019
DOI: 10.3390/en12224335
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Water Cycle Optimization Algorithm for Optimal Placement of Wind Turbines in Wind Farms

Abstract: Wind farms (WFs) include an enormous number of wind turbines (WTs) in order to achieve high capacity. The interaction among WTs reduces the extracted amount of wind energy because wind speed decreases in the wake region. The optimal placement of WTs within a WF is therefore vital for achieving high performance. This permits as many WTs as possible to be installed inside a narrow region. In this work, the water cycle algorithm (WCA), a recently developed optimizer, was employed to identify the optimal distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…The CMRFO5 achieved a power generation of 18337KW with 86.28% efficiency for a cost equal to 0.0015306, while MRFO produced a total power of 17880KW and 86.23% efficiency for a cost equal to 0.0015375. Along with these findings, it is observed that the cost per unit power is improved compared to those reported in the literature and the re-implemented approaches and has been decreased by 11.92% for Mosetti et al [2], 2.19% for Grady et al [4], 2.18% for Pookpunt et al [14], 0.10% for Taleb et al [30], 1% for Kalyan et al [31], 0.23% for Biswas et al [38], 0.46% for Hegazy et al [43], and 1.95%, 2.48%, 1.5% for AOA, SCA, and SSA, respectively. It is worth noting that the results are compared for unfixed WTs.…”
Section: ) Scenario 1 : Constant Wind Speed Variable Directionmentioning
confidence: 69%
See 2 more Smart Citations
“…The CMRFO5 achieved a power generation of 18337KW with 86.28% efficiency for a cost equal to 0.0015306, while MRFO produced a total power of 17880KW and 86.23% efficiency for a cost equal to 0.0015375. Along with these findings, it is observed that the cost per unit power is improved compared to those reported in the literature and the re-implemented approaches and has been decreased by 11.92% for Mosetti et al [2], 2.19% for Grady et al [4], 2.18% for Pookpunt et al [14], 0.10% for Taleb et al [30], 1% for Kalyan et al [31], 0.23% for Biswas et al [38], 0.46% for Hegazy et al [43], and 1.95%, 2.48%, 1.5% for AOA, SCA, and SSA, respectively. It is worth noting that the results are compared for unfixed WTs.…”
Section: ) Scenario 1 : Constant Wind Speed Variable Directionmentioning
confidence: 69%
“…[30], Kalyan et al [31], Biswas et al [38], Hegazy et al [43], AOA, SCA, and SSA, respectively. According to the studies mentioned above, Mosetti reported higher efficiency of up to 94.65% with a lower total power output of 13588KW for 15 turbines.…”
Section: ) Scenario 1 : Constant Wind Speed Variable Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…WCA is one of the promising heuristic optimization techniques especially in power system area. WCA has been introduced to solve optimal microgrids integration considering emission cost, reliability and loss minimization [11][12][13][14]. Gravitational Search Algorithm is another heuristic-based optimization technique that has been implemented for scheduling, sizing and citing of DGs [15][16][17][18][19][20].…”
Section: Pgmentioning
confidence: 99%
“…It was shown that innovative solutions dealing with turbines, such as a lubrication system for hollow roller bearings, can lead to increased energy efficiency and system output [17,18]. Different algorithms have been employed to find the optimal layout of wind farm and placement of wind turbines for different regions [19,20]. Furthermore, impacts of climate change on wind energy resources have been evaluated using different GCMs and also regional climate models for different areas all over the world.…”
Section: Introductionmentioning
confidence: 99%